Identification of hypervirulent Klebsiella pneumoniae carrying terW gene by MacConkey-potassium tellurite medium in the general population - Wu, Xiufeng; Zhan, Fuguo; Zhang, Jiawei; Chen, Shanjian; Yang, Bin (Frontiers in Public Health, 2022)
Objectives： To establish a MacConkey-potassium tellurium medium-based method for selectively culturing terW gene-positive Klebsiella pneumoniae (KP), to evaluate its performance and apply it to identifying particular clonal hypervirulent KP (hvKP) strains in epidemiological surveillance. Methods： The virulence genes, rmpA, iutA and terW, were detected by PCR. The minimum inhibitory concentration of potassium tellurite of hvKP (rmpA+/ iutA+) and classical KP (rmpA- and iutA-) was determined by agar dilution method. The MacConkey medium containing 4 μg/ml potassium tellurite was prepared and the performance in detecting terW+ KP was evaluated, including agreement with PCR and positive/negative predictive value. Fecal samples from healthy volunteers in Fujian were collected and cultured in the medium, then positive strains were identified by MALDI-TOF MS, antimicrobial susceptibility were tested by Kirby-Bauer assays, and virulence genes and capsular serotype genes were tested by PCR. Results: In KP isolated from clinical specimens (N=198), the positive rate of terW was 37.9%, and the detection rate of terW in hvKP was significantly higher than that in classical KP (70.6% vs 13.3%). The potassium tellurite resistance levels of terW+ (N=75) and terW- (N=55) KP were 8 128 μg/ml and <1 μg/ml 8 μg/ml, respectively, with significant differences. KP was selectively cultured on a MacConkey medium with 4 μg/ml potassium tellurite, and its agreement with PCR was good (Kappa=0.936), and the positive and negative percent agreement, and positive and negative predictive value were 100% (75/75), 92.7% (51/55), 94.9% (75/79) and 100% (51/51), respectively. The prevalence of tellurite-resistant KP was 16.7% (86/516) in fecal samples from healthy volunteers, among which the positive rate of terW was 100% (86/86). The antimicrobial resistance characteristics of terW+ KP showed no difference between healthy volunteers and inpatients. The most common capsular serotypes associated with high virulence were K1, K2 and K57. Conclusions: The MacConkey medium containing 4 μg/ml potassium tellurite could easily select and culture terW+ KP in fecal samples with high sensitivity and specificity, which is a practical method for the epidemic surveillance of hvKP in general population.